Predictors of intention to provide halal maintenance - Ahmad, Sa’odah; Johari, Mohammad Arif; Kahar, Rojanah; Hasbullah @ Abdullah, Muslihah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This study examined the relationship between attitude, subjective norms and perceived behavioral control with the intention to provide halal maintenance to the family among Muslim fathers in Malaysia. The participants comprised of 353 Muslim fathers. The data were collected via a self-administered questionnaire. Findings from the study showed that there was a positive relationship between attitude, subjective norms and perceived behavioral control with the father's intention to provide halal maintenance for the family. In addition, the subjective norm is proven to be the most significant predictor of the intention to provide halal maintenance for the family.